The Effect of Taxation on Labor Supply: Evaluating the Gary Negative Income Tax Experiment - Burtless, Gary; Hausman, Jerry A. (Journal of Political Economy, 1978)
A model of labor supply is formulated which takes explicit account of nonlinearities in the budget set which arise because the net, after-tax wage depends on hours worked. These nonlinearities may lead to a convex budget set due to the effect of progressive marginal tax rates, or they may lead to a nonconvex budget set due to the effect of government transfer programs such as AFDC or a negative income tax. The nonlinearities affect both the marginal wage and the "virtual" nonlabor income which the individual faces. The model is estimated on a sample of prime-age males from the Gary negative income tax experiment.